Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 2 - Section 2.3 - The Algebra of Functions - Exercise Set - Page 133: 36


$(f-g)(x)=x^{2}+5x-2$ $(f-g)(6)=64$

Work Step by Step

$(f-g)(x)=f(x)-g(x)$ $=x^{2}+4x-2+x$ $=x^{2}+5x-2$ Plugin $x=6$ into $x^{2}+5x-2$. $(f-g)(6)=6^{2}+6\times5-2=36+30-2=64$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.